The effects of ambient temperature and lighting intensity on wheel-running behavior in a diurnal rodent, the Nile grass rat (Arvicanthis niloticus) - Fogo, Garrett M; Goodwin, Alyssa M; Khacherian, Ohanes S; Ledbetter, Brandi J; Gall, Andrew J (Journal of comparative psychology (Washington, D.C. : 1983), 2019)
Environmental conditions, such as the light-dark cycle and temperature, affect the display of circadian rhythmicity and locomotor activity patterns in mammals. Here, we tested the hypothesis that manipulating these environmental conditions would affect wheel-running activity patterns in a diurnal rodent, the Nile grass rat (Arvicanthis niloticus). Grass rats are diurnal in the field, however, a subset switch from a day-active pattern to a night-active pattern of activity after the introduction of a running wheel. The mechanism of this chronotype switch remains largely unknown. In the present study, grass rats were presented with running wheels in 12:12 light-dark conditions. First, subjects were exposed to 25 °C during the day and 21 °C at night, which resulted in 100% of grass rats expressing diurnal behavior. Subjects were then exposed to manipulations of elevated ambient temperature, which resulted in a significant reduction in wheel-running activity. Reducing ambient temperature below 21 °C, however, did not disrupt the expression of diurnality or overall activity. Next, lighting intensity was reduced, which resulted in a switch from a diurnal to a nocturnal chronotype in a subset of animals and reduced overall wheel-running activity. Upon return to baseline lighting intensity, patterns of diurnal activity were restored. Altogether, increases in ambient temperature and decreases in lighting intensity significantly reduced overall wheel-running activity. Importantly, dim light resulted in a temporal niche switch in a subset of grass rats, suggesting a critical role for lighting intensity on the expression of wheel-running activity patterns. (PsycINFO Database Record (c) 2019 APA, all rights reserved).